PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN CLASSPOINT AI UNTUK GURU SEKOLAH MENENGAH - Dina Octaria; Rohana; Tika Dwi Nopriyanti; Allen Marga Retta; Nora Surmilasari; Tanzimah (LP3MKIL, 2025)
The digital transformation in education demands that teachers be able to utilize technology to create interactive and engaging learning experiences. This community service program aimed to enhance the competence of teachers at SMA Negeri 3 Prabumulih in developing interactive learning media using ClassPoint AI. The program was implemented through a series of training sessions involving lectures, demonstrations, discussions, and hands-on practice. The results showed an improvement in teachers’ ability to create creative and functional instructional media by leveraging the interactive features of ClassPoint AI. These findings affirm that integrating technology can be an effective solution to the limitations of conventional teaching methods and can encourage innovation in the learning process. To ensure the sustainability of the program’s impact, further development of the created media and follow-up training are necessary to strengthen teachers’ digital skills.